2014
DOI: 10.1038/pr.2014.11
|View full text |Cite
|
Sign up to set email alerts
|

Role of per-rectal portal scintigraphy in long-term follow-up of congenital portosystemic shunt

Abstract: Background: Congenital portosystemic shunt (CPSS) has the potential to cause hepatic encephalopathy and thus needs long-term follow-up, but an effective follow-up method has not yet been established. We aimed to evaluate the importance of per-rectal portal scintigraphy (PRPS) for long-term follow-up of CPSS. Methods: We retrospectively examined shunt severity time course in patients (median: 9.6 y, range: 5.2-16.6 y) with intrahepatic (n = 3) or extrahepatic (n = 3) CPSS by using blood tests, ultrasonography o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In order to evaluate the shunt severity in addition to the presence of PSS, per-rectal portal scintigraphy using 99m Tc-pertechnetate was performed, and the amount of radionuclide shunting the liver and reaching the systemic blood after injection into the rectum was measured as described previously. 6 On per-rectal portal scintigraphy shunt index was elevated, at 21.4% (cut-off >10%), thus supporting the presence of intrahepatic PSS. At patient age 12 months, laboratory examination showed mild elevation of liver enzymes (AST, 72 IU/L; ALT, 58 IU/L), total bilirubin, 0.2 mg/dL, TBA, 33.3 μmol/L; GGTP, 36 IU/L; α-fetoprotein, 7.4 ng/mL; and ammonia, 69 μg/dL.…”
Section: Case Reportmentioning
confidence: 88%
See 1 more Smart Citation
“…In order to evaluate the shunt severity in addition to the presence of PSS, per-rectal portal scintigraphy using 99m Tc-pertechnetate was performed, and the amount of radionuclide shunting the liver and reaching the systemic blood after injection into the rectum was measured as described previously. 6 On per-rectal portal scintigraphy shunt index was elevated, at 21.4% (cut-off >10%), thus supporting the presence of intrahepatic PSS. At patient age 12 months, laboratory examination showed mild elevation of liver enzymes (AST, 72 IU/L; ALT, 58 IU/L), total bilirubin, 0.2 mg/dL, TBA, 33.3 μmol/L; GGTP, 36 IU/L; α-fetoprotein, 7.4 ng/mL; and ammonia, 69 μg/dL.…”
Section: Case Reportmentioning
confidence: 88%
“…a). In order to evaluate the shunt severity in addition to the presence of PSS, per‐rectal portal scintigraphy using 99m Tc‐pertechnetate was performed, and the amount of radionuclide shunting the liver and reaching the systemic blood after injection into the rectum was measured as described previously . On per‐rectal portal scintigraphy shunt index was elevated, at 21.4% (cut‐off >10%), thus supporting the presence of intrahepatic PSS.…”
Section: Case Reportmentioning
confidence: 99%
“…Imaging can be used to measure shunt size. Per-rectal scintigraphy may provide indirect quantification of the shunt ratio (also called shunt fraction or shunt index), i.e., the degree of flow traversing the shunt [ 1 , 12 , 87 , 88 ]. How this ratio is related to clinical signs and symptoms is unclear and still a matter of debate among experts.…”
Section: Approach For the Clinicianmentioning
confidence: 99%
“…Shunt ratios of greater than 5% were considered abnormal [ 13 , 15 ]. This method has gradually been replaced by the Doppler ultrasound although one study demonstrated (Yuki Cho et al) superiority in the estimation of shunt severity using rectal scintigraphy [ 12 , 14 , 52 ].…”
Section: Diagnosismentioning
confidence: 99%